Grieving Process Among Bereaved Family in The Funeral Ceremony Amid Covid-19 Pandemic: A Literature Review - Tutu April Ariani; Ika Rizki Anggraini (Malahayati Nursing Journal, 2023)
ABSTRACT Sudden death due to COVID-19, will have an impact on the family and causes grief, devastating and traumatic. To prevent the Coronavirus high transmission rate during pandemic has provided a new perspective on dying and rituals worldwide and needs reform. Funeral practices that should give comfort and support were not possible, which can increase feelings of isolation, loss, and despair on family. This study aims to find out what information already exists in the bereaved family grieving process related to the funeral ceremony policy during the COVID-19 pandemic. This study used literature review from 21 articles from four electronic databases: MEDLINE (Ovid), Embase, EBSCOhost, and Scopus, and added the search from other references as grey literature. The literature was reviewed chronologically to demonstrate how grieving process went through by bereaved family related to the funeral policy during COVID-19 pandemic. The findings of the selected literature review and equipped with grey literature, shows how family involvement in each funeral’s stage of the deceased: planning, within and post ceremony, having a relationship and impact on the priesthood and success of the grieving process on the family left by Covid-19. We underline that it is essential to be present in the burial process, starting from involvement in planning, attending, and believing the funeral process and after it is necessary to note. Future research is still needed to review more literature with a mix-method study. Thus, it can equally review both studies to balance and mutually supportive Keywords: Bereaved Family, COVID-19, Funeral Ceremony, Grieving Process, Literature Review